Experimental pathogenicity of Candida albicans and Candida dubliniensis with continuous and discontinuous fringes morphotypes - Vasconcellos, Thassia Castro de [UNESP]; Komiyama, Edson Yukio [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP]; Brighenti, Fernanda Lourenção [UNESP]; Vidotto, Valerio; Koga-Ito, Cristiane Yumi (Wiley-Blackwell, 2011)
A possible correlation between the presence of discontinuous fringes and high virulence has been previously suggested. The aim of this study was to compare the pathogenicity of Candida albicans and Candida dubliniensis with continuous and discontinuous fringes morphotypes on mice. For C. albicans, two discontinuous fringe morphotype isolates (PN 69, PN 74), two continuous fringe morphotype isolates (N 60, N 33) and one reference strain were used. For C. dubliniensis, three discontinuous fringe morphotype isolates (97487, 97464, 97519), two continuous fringe morphotype isolates (97040, 98026) and one reference strain were used. Swiss male mice were inoculated with a standardised suspension of the microorganisms and observed for 35 days. The pathogenicity of the isolates was analysed according to parameters proposed previously. Three isolates were considered pathogenic: PN 74, N 60 and 98026. Strain N 60 killed the highest amount of mice (80%). Animals inoculated with C. albicans did not show differences on survival estimate. Candida dubliniensis 98026 was more pathogenic than samples 97464 and 97519. on the other hand, the sample 97487 showed a higher pathogenicity when compared with 97040 (Kaplan-Meier test, P = 0.008). Strains with continuous fringe morphotypes were also associated with Candida sp. virulence in vivo.
Keywords: Candida; mycological typing techniques; virulence